Poklicna rehabilitacija bolnikov z rakom - Rozman, Sanja (Rehabilitacija (Ljubljana), 2008)
Vocational rehabilitation includes all activities that help disabled persons secure, retain and advance in a suitable employment and in that manner support their integration into society. For most cancer survivors, work is a financial and emotional necessity; they keep working not only for the financial benefit but also for the accompanying self-esteem and social support. In the past 30 years, the percentage of cancer survivors returning to work has kept rising: 75% survivors and 40% family members have been said to change their employment status due to the disease consequences. 886 cancer survivors have been assessed on pension boards in Slovenia in 2006, 483 of them were found unfit to continue working, 339 persons were granted the right to a change in working conditions, (including reduced working hours), and 64 were sent to some form of vocational training. The majority of them have been diagnosed with intestinal cancers (19%), the survivors of lung cancers were most frequently found unfit for professional work. The experience of living with cancer brings long-term changes in the life of a survivor, but the extent of the consequences is difficult to predict. Cancer is a common name for a great number of different diseases with different consequent disabilities. However, consequences differ greatly even among patients with similar or comparable clinical stage disease, and it is not enough to consider the clinical information only (the biology and stage of the disease) to understand whether the survivor will be able to resume working. Other factors concerning personal and social situations of the survivor, as well as the conditions at his or her workplace, contribute significantly to the rehabilitation outcomes, especially to the ability to return to work. The new ICF classification is a base for the changes in perspective, offering the possibilities to consider the interplay of biological, as well as personal and environmental factors, in the life of the survivor. In practice, the options for return to work are defined in the national legislation. Complex assessment of functional abilities, work endurance and effectiveness, learning abilities, work behavior and attitudes, necessary environmental adjustments can be performed by a team of experts at the Institute for Rehabilitation.
Keywords: bolniki; poklicna rehabilitacija; rak (medicina)